THE TEACHER’S ROLE IN MANAGING THE CLASS WITH AN INNOVATIVE APPROACH - Wahyuni, Nur; Siallagan, Sintia (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2023)
This study explores the role of teachers in managing classrooms with an innovative approach to enhance student learning in the contemporary era. The primary focus is on the innovative strategies teachers employ to create a dynamic learning environment that stimulates student interest and encourages active participation. Through a review of literature and case studies, this research identifies several effective practices used by teachers, such as the integration of educational technology, project-based learning, student collaboration, and the application of various assessment strategies that support competency-based learning. The findings highlight the importance of teachers’ roles as classroom managers who can quickly adapt to technological and educational advancements while fostering creativity and innovation in the learning process. The implications of these findings for teacher professionalism development and improvements in the contemporary education system are also discussed.